Chapter Damasias and Thales: stasis and sophia at the term of Solon's apodemia - Leão, Delfim (Studi e saggi, 2022)
This paper addresses an obscure aspect surrounding Solon's activity, which occurred after his political and legislative activity and before his opposition to Pisistratus' moves towards tyranny. It tackles, more specifically, the way in which Solon may have been indirectly involved (as a politician but also as a sophos) in a triangle of interests that would include, besides himself, two personalities associated with a period of stasis (Damasias) and with the status of sophos (Thales). In order to achieve this goal, the present study combines two different approaches: it first analyses the historical circumstances that marked Athens during the period immediately after Solon's legislation, until the moment when Damasias held the archonship, and then clung to office for a further year and two months; it then discusses the testimony of Demetrius of Phalerum (quoted by Diogenes Laertius, 1.22), according to whom Thales was named for the first time sophos during the archonship of Damasias.